Adaptive time and frequency resource assignment with COFDM for LMDS systems. - Tralli, V.
In this letter, a wireless local multipoint distribution system (LMDS) at millimeter waves for the last-mile broad-band distribution to users of interactive services is investigated. The system analyzed employs a coded orthogonal frequency-division multiplexing transmission scheme with frequency-division multiplexing (FDM) and/or time-division multiplexing techniques and adaptive carrier allocation to counteract the effects of the wireless communication channel. The idea of deploying the reverse channel (exploited by the user for interactivity purposes) to provide channel information to the broadcasting transmitter is introduced. System performance is evaluated for an urban microcellular radio system in an actual propagation environment and the choices of the optimum multiplexing technique and carrier allocation algorithm are discussed in the case of ideal feedback. It is found that a pure FDM technique combined with an adaptive carrier allocation algorithm giving priority to users having the largest path loss leads to the best performance
Keywords: COFDM; LMDS systems; Adaptive carrier allocation; Adaptive carrier allocation algorithm; Adaptive time resource assignment; Carrier allocation algorithm; Coded orthogonal frequency-division multiplexing transmission scheme; Frequency resource assignment; Frequency-division multiplexing; Interactive services; Last-mile broad-band distribution; Millimeter waves; Optimum multiplexing technique; Path loss; Reverse channel; System performance; Time-division multiplexing; Urban microcellular radio system; Wireless communication channel; Wireless local multipoint distribution system